The Winding Path to Degree: Obstacles to Higher Education for Low-Income Single Mothers. Issue 32020 (1st September 2020) - Freeman, Amanda
Abstract : Single mothers have the lowest rates of degree completion of any demographic group when they pursue higher education as a path out of poverty. This article explores the obstacles student mothers face when they pursue higher education. The lived experiences of participants add context to data about low rates of degree completion. Findings are based on a 3-year qualitative study, including 66 in-depth interviews with 37 unique participants of an anti-poverty program in Boston, Massachusetts. The study utilized a feminist action research framework, focusing on the marginalized voices of the students, combined with a constructivist grounded theory approach to collecting and analyzing the data. Obstacles to the mothers' pursuit of higher education emerged in the following categories: (a) inflexible institutions, (b) dead ends, and (c) lack of career guidance. Suggestions for higher education institutions, government policies, and nonprofit organizations to better support single mother students are discussed.